School Leadership in Crisis: A Job Demands-Resources Model of Saskatchewan School Administrators’ Work, Stress, and Burnout - Swapp, Donna H.; Osmond-Johnson, Pamela (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
This article mobilizes the Job Demands-Resources (JD-R) model and draws on data from a longitudinal study of Saskatchewan school administrators’ work and wellbeing to situate and trouble the enduring nature of high job demands, low job resources, and stress for incumbents in this province. Our findings point to serious implications of continued inattention to issues of stress, with school administrators either retiring from, leaving, or expressing their desire to leave, the role. We position this reality as unfolding within an overarching neoliberal school leadership context that promotes efficiency, accountability, and productivity over school leader workload and wellbeing and caution that this troubling reality does not reside solely in and with the school principalship but can morph into a larger school system crisis if not urgently addressed.